The debilitating effects of chronic diseases among the oldest old in China - Tey, Nai Peng; Lai, Siow Li; Teh, Jane Kimm Lii * (Elsevier, 2016)
Objectives The aims of this study were to assess the current sharp rise in chronic diseases and disabilities with advancing age, and to examine the debilitating effects of chronic diseases among the oldest old in China.